BEBERAPA FAKTOR YANG BERHUBUNGAN DENGAN KEKURANGAN ENERGI KRONIS PADA IBU HAMIL - Gustini Gustini; Lia Fitria; Irnawati Irnawati; Siska Sibua (Ensiklopedia Research and Community Service Review, 2026)
Abstract: Chronic Energy Deficiency (CED) is one of the most common nutritional problems among pregnant women and remains a concern in the field of public health. CED is a condition characterized by a long-term deficiency in energy and nutrient intake—particularly protein—resulting in the body’s nutritional needs not being optimally met. The purpose of this study was to identify factors associated with chronic energy deficiency in pregnant women. A cross-sectional study design was used in this research. The study was conducted in the service area of the Martapura I Community Health Center (Puskesmas). The study was carried out in August 2025. The study population consisted of all pregnant women registered at the Martapura I Community Health Center. The sample comprised 60 respondents. Purposive sampling was used. The research instrument used was a questionnaire. Data analysis was performed using univariate and bivariate methods. The results indicated an association between parity (p-value: 0.004) and birth spacing (p-value: 0.039) and the incidence of chronic energy deficiency (CED) among pregnant women. It is recommended that community health centers provide more motivation and encouragement to pregnant women by equipping them with the knowledge and understanding needed to monitor their pregnancies, recognize warning signs and risks, and manage KEK during pregnancy. The hope is that this will lead to greater adherence to a nutritionally balanced diet among pregnant women, improve communication skills with the community, and serve as input for future research.Keywords: Pregnant Women, Chronic Energy Deficiency, Parity.